The Impact of Sunitinib N-oxide as a Photodegradation Product of Sunitinib - Miki Takenaka; Yuta Takahashi; Hideaki Yashima; Takuya Araki; Koujirou Yamamoto (Universitas Padjadjaran (Unpad), 2019)
During treatment with sunitinib, dosage adjustment according to the monitored blood concentration of sunitinib and SU12662 is considered useful. On the other hand, the appearance of hand-foot skin reaction (HFSR) cannot be explained by blood sunitinib concentration alone. Although light exposure greatly affects skin disorders associated with medication use, the photodegradation of sunitinib has not been studied in detail. Here, we investigated the photodegradation products of sunitinib using LC-MS and examined cytotoxic activities using an MTT assay. N-desethyl sunitinib and sunitinib N-oxide were identified as photodegradation products, and their concentrations increased under irradiation in a time-dependent manner. Although the IC50 value of N-desethyl sunitinib in the HEK 293 cell line (11.6 µmol/L) was similar to that of sunitinib (8.6 µmol/L), the IC50 value of sunitinib N-oxide (121.9 µmol/L) was over 10 times higher than that of sunitinib. In addition, N-desethyl sunitinib and sunitinib N-oxide were found in blood obtained from a patient taking sunitinib (24.7 and 2.3 ng/mL, respectively). Because the appearance of adverse drug reactions associated with sunitinib can be reduced by using α-tocopherol nicotinate, which has a strong antioxidant effect, we believe that sunitinib N-oxide might strongly promote the development of HFSR.Keyword : sunitinib, sunitinib N-oxide, photodegradation product, light